From Nature to Tourism: Exploring Geographical Potential to Enhance the Attraction of Nature Tourism - Arif Putranto; Michael Oluwabukunmi Lawal (Journal of Social Knowledge Education (JSKE), 2024)
Purpose of the study: The purpose of this study is to identify the development potential of the Cipondoh Lake area by studying a number of factors, namely physical characteristics, socio-cultural, accessibility, facilities, and ecological conditions in the Situ Cipondoh area. Methodology: The research method used is a descriptive method with a qualitative approach. The sampling technique used is the accidental technique, then the data that has been analyzed is presented in a descriptive analysis using a single frequency table. The data presented is then interpreted based on existing theories and measured with appropriate presentation. Data collection in this study was carried out using questionnaires, interviews, observations, and documentation. Main Findings: The results found in this study indicate that the physical condition of Situ Cipondoh's potential has a score of 11, which means it is not yet sufficiently supportive. Furthermore, the socio-cultural potential gets a score of 40, which means it is supportive. The accessibility potential gets a score of 13, which means it is very supportive, and the existing facility score is 10, which means it is supportive. The total overall score is 74, which indicates that Situ Cipondoh is supportive and worthy of being a tourist area. Novelty/Originality of this study: This research provides novelty by exploring geographical potential as a major factor in increasing the attractiveness of natural tourism, which previously received less attention in the development of natural resource-based tourist destinations.